(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Upper endoscopy is an essential, safe and sensitive tool for diagnosing pediatric gastrointestinal issues. In Bangladesh, the practice of pediatric endoscopy remain rudimentary due to lackoftrained pediatricendoscopist. There is limited study on pediatric upper GI endoscopy in our country. The aim of the study was to find out the indications, common endoscopic findings and immediate post procedure complication of UGI endoscopy in children. Materials and methods: This is a retrospective study, the medical records of all patients whose age is under 18 years and who underwent upper GI endoscopy in last 2 years were included. Results: Among the total of 150 children (Age <18 years), the most common indications were recurrent abdominal pain in 95 (63.3%) patients followed by Vomiting 26(17.33%), hematemesis 22(17.67%), dysphagia 4(2.7%), jaundice 3(2%). In almost half of the patients 75 (50%), the endoscopic findings were normal. The most common abnormal endoscopic findings were esophagitis seen in 42(28%) of patients followed by 18(12%) cases of superficial gastritis, duodenal ulcer 5 (3.3%), esophageal varix 4(2.6%), gastric polyp 3 (n=2%), antral gastritis 1(0.7%), biliary ascariasis 1(0.7%), esophageal ulceration 1(0.7%). Conclusion: The commonest indication for Pediatric UGI endoscopy was recurrent abdominal pain and the commonest endoscopic feature was esophagitis. No significant post procedure complication was noted in this study. Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 75-78